Variations in Colorectal Cancer Screening of Medicare Beneficiaries Served by Rural Health Clinics. (21st July 2015) - Wan, Thomas T. H.; Ortiz, Judith; Berzon, Rick; Lin, Yi-Ling
This study aims (1) to examine the trends and patterns of colorectal cancer screening (CCS) of Medicare beneficiaries in rural areas by state and year (before and after Affordable Care Act [ACA] enactment) and (2) to investigate the contextual, organizational, and aggregated patient characteristics influencing variations in care received by patients of rural health clinics (RHCs). The following 2 hypotheses were formulated: (1) CCS rates are higher in the post-ACA period than in the pre-ACA period, irrespective of the factors rurality, poverty, dually eligible status, and the organizational characteristics of RHCs and (2) the contextual and organizational factors of RHCs exert more influence on the variation in CCS rates of RHC patients than do aggregated personal factors. We used administrative data on CCS rates (2007 through 2012) for rural Medicare beneficiaries. Autoregressive growth curve modeling of the CCS rates was performed. A generalized estimating equation of selected predictors was analyzed. Of the 9 predictors, 5 were statistically significant: The ACA and the percentage of female patients had a positive effect on the CCS rate, whereas regional location, years of RHC certification, and average age of patients had a negative effect on the CCS rate. The predictors accounted for 40.2% of the total variance in CCS. Results show that in rural areas of 9 states, the enactment of ACA improved CCS rates, contextual, organizational, and patient characteristics being considered. Improvement in preventive care will be expected, as the ACA is implemented in the United States.